148k views
5 votes
Are these two quadratic expressions
equivalent? Explain.
(x+3)(x-4)
x2 + 7x - 12

User Arlistan
by
4.8k points

1 Answer

5 votes

I know the 1st one.

Answer:

(x+3)(x-4) = x-12

Explanation:

This is called a foil method

1st: We multiply the two first numbers - x*x = 2x

2nd: We multiply the two outside numbers - x*(-4) = -4x

3rd: We multiply the two inside numbers - 3*x = 3x

4th: We multiply the two last numbers - 3*(-4) = -12

Then we combine them - 2x-4x+3x-12

Then we simplify - x-12

Hope this helped!

User Rohan Khude
by
5.9k points